Penerapan Akuntansi Syariah pada Perbankan di Indonesia dan Malaysia atas Transaksi Mudharabah - Suryanto, Prasetyo Dwi; Asyik, Nur Fadjrih; Wahidawati, Wahidawati (ITB AAS INDONESIA Surakarta, 2024)
This paper discusses the application of sharia accounting on mudharabah transactions in Islamic banking in Indonesia and Malaysia. Mudharabah is one of the flagship products in the Islamic banking industry in both countries. Proper implementation of accounting for mudharabah transactions is crucial to maintain transparency, accountability, and compliance with sharia principles. This study aims to analyze the application of sharia accounting on mudharabah transactions in Islamic banking in Indonesia and Malaysia. The research method used is a literature study by collecting data from various sources such as regulations, accounting standards, and related literature. The results show that there are similarities and differences in the application of sharia accounting on mudharabah transactions between Indonesia and Malaysia. The similarities include the recognition, measurement, and presentation of mudharabah transactions which are guided by the respective country's sharia accounting standards. The differences lie in the regulations, implementation practices, and disclosure of information related to mudharabah transactions in the financial statements.